'In the mix': Relational leadership explored through an analysis of techno DJs and dancers. (June 2019) - Biehl, Brigitte
Relational leadership theory views leadership as a process of social construction in which participants engage through their bodily presence. The 'in-between' space connecting leaders and followers, however, is under-researched and has not been analysed with a focus on movement. With a phenomenological approach and dance theory, this study explores movement by considering techno DJs and their live performances to an audience in clubs. It analyses DJs' insights into relationships between themselves and followers. DJs actively seek physical proximity and use bodily movement and kinaesthetic empathy to relate to the participants, engage in mutual challenge, and embrace the co-creation that emerges. These insights are transferable to many leadership situations that include embodied interaction. The study illustrates that leaders not only 'have' bodies, but 'are' (moving) bodies who achieve a profound appreciation of the situation. This changes how we conceive of leadership when agency in embodied interaction is conditioned and reciprocated by leaders and followers in the 'in-between' space and does not pertain to one or the other.